Nurturing Equality, Diversity and Inclusion Support for Research Careers in Health and Biomedicine - Thomson, Aleksandra (Policy Press, 2024)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This book provides scientific evidence to support arguments for equality and change in academic institutions both in terms of the business case and the interests of social justice. Familiarising readers with the key equality, diversity and inclusion (EDI) issues in health and biomedicine in relation to research careers and researcher development, it is an essential guide for equality planning team members, researchers, HRM officers and managers across academia.